FORMALIZATION OF THE MASTER PRODUCTION SHEDULE FORMATION TASK IN THE MRP II PLANNING SYSTEM - Novinskyi, V. P.; Popenko, V. D. (Radio Electronics, Computer Science, Control, 2024)
Context. Considered the task of forming the Master Production Shedule in the process of production management based on the MRP II standard. The object of the study is the algorithm for forming this plan for further planning of materials supply for production and the organization of production itself. Objective. Improvement of the algorithm of Master Production Shedule formation to avoid unnecessary stages of the algorithm. Method. It is proposed to improve the algorithm of the Master Production Shedule formation. It consists in simultaneously taking into account the requirements for timely delivery of products to customers, limitations regarding the capacities of the company’s work centers, and limitations regarding the duration of procurement cycles in the process of supplying materials. The MRP II standard envisages first planning the terms and quantity of product releases, and only at the next step checking the formed plan for admissibility with regard to the required time of operation of the equipment and the availability of the required materials quantity. In case of the calculated plan limitations violation, it is necessary to either plan and implement measures to overcome the specified limitations, i.e. organize additional shifts for work centers, use additional capacities, speed up the delivery of some materials, or reduce the sales plan. All these measures are associated with additional costs. In the proposed version of the planning process, this should be done only if the algorithm does not find an acceptable solution. The task of forming the Master Production Shedule, which is central to the MRP standard, is formulated by the authors as a linear programming task due to the linear nature of the specified restrictions on production capacities and materials. In particular, in the case of sufficiently severe restrictions on the work centers capacity, the plan for replenishing the remaining products from production is shifted to earlier planning intervals and only then rests against the restrictions. Several strategies are proposed for planning replenishments from the production of products stock. Results. The developed algorithms are implemented in the form of Microsoft Excel templates and are available for use in order to deepen the understanding of the MRP II standard. They are also used in the educational process. Conclusions. Approbation of the solution by the authors confirmed its workability, as well as the expediency of implementing the developed modification of the MRP II planning process into the software of leading ERP class systems suppliers. Prospects for further research may consist in a comparative analysis of the proposed options for placement of products replenishment from production, through economic evaluation of these options, as well as through simulation modeling.